Effect of knee strengthening exercises with and without hip Strengthening exercises in women with knee osteoarthritis: randomized controlled trials - Umer Hayat, Mariam; Ashfaq, Anam; Manzoor, Maria; Arshad, Kanwal; Hanif, Kamran (Journal of University Medical & Dental College, 2023)
Background and Objective: Hip strengthening exercises in patients with knee osteoarthritis is very beneficial the aim of study to determine combine effects of hip strengthening exercises with knee strengthening exercises on knee pain, function and activities of daily livings and quality of life in women with knee osteoarthritis. Methodology: In total, seventy women aged 40-70 year with knee OA, II–III grades on the Kellgren-Lawrence scale were included and randomized to experimental group (EG) and control group (CG) 35 in each group. The participants were going for 6-week supervised session, 4 times per week. The strengthening program consisted knee with hip strengthening exercises for EG, and only knee strengthening exercise for CG. Elastic Thera-Bands were used for resistance. KOOS was used for assessment and perform at baseline, 2nd week, 4th week and 6th week. Results: Finally 61 subjects were completed the study 31 in EG and 30 in CG. Results show that there were statistically and clinical significant improvements in the KOOS score in both groups from baseline to at 6th week. There was significant difference were observed in experimental group with mean pain 36.94±8.718 to 82.19±7.472 (p=0.051) in EG, & 22.97±4.165 to 72.53±5.237 (p=0.004) CG. The mean function 29.71±9.389 to 81.19±6.036 (p=0.000) EG & 24.14±4.927 to 67.94±3.984 (p=0.003) in CG and the mean Quality Of Life 27.06 ±7.806 to 60.61±10.148 (p=0.005) in EG & 24.30± 6.271 to 67.27± 7.821(p=0.000) in CG respectively. Conclusion(s): The combined knee strengthening exercise with hip strengthening exercises provide more significant enhancement in the clinical outcomes that are pain, function of daily living and quality of life in the women with osteoarthritis of the knee.